TEDxUniversityoftheAegean | Chios Pre-Event 2016 (TEDx UniversityoftheAegean, 2016)
: Can't reach without you Higher Can't reach without you Higher Can't reach without you Didn't I take you to Higher places you Didn't I take you to Higher places you Can't reach without you Didn't I take you to Higher places you Didn't I take you to Higher places you Didn't I take you to Higher places you Didn't I take you to